Revitalizing Arabic Learning in Madrasah: A Deep Learning-Based Holistic Framework Integrating Islamic Pedagogy - Hania, Irfan; Ubaidillah, Ubaidillah; Mufrodi, Mufrodi; Faiqotussana, Faiqotussana; Rifaldi, Muhammad (HEUTAGOGIA: Journal of Islamic Education, 2025)
This study aims to formulate the "Arabic Language Learning as a Holistic Experience" conceptual framework to revitalize pedagogy in madrasahs, aligning with the national Deep Learning campaign. Using a conceptual framework development method, this research conducts a thematic synthesis and argumentative analysis of literature from educational psychology and Islamic pedagogy. The main results are three synthesized propositions: (1) Meaningful Learning is enriched by tadabbur (contemplation) to achieve spiritual meaningfulness; (2) Mindful Learning is integrated with khusyū' (reverent presence) to create full presence; and (3) Joyful Learning is reinterpreted through ladzdzah al-‘ilm (the pleasure of knowledge) to cultivate intellectual-spiritual delight. These propositions are constructed into a holistic model that views the Arabic language as an integrated experience rather than merely a school subject. Its practical implications include shifting the teacher's role to that of a facilitator-murabbī (spiritual guide) and reorienting assessment, while theoretically, the model bridges the discourse of modern psychology with Islamic wisdom. As a conceptual study, its primary limitation is the lack of empirical validation; therefore, future research is recommended to test the framework's effectiveness through classroom-based intervention studies.